INTENTION IN STOCK INVESTMENTS INFLUENCED BY FINANCIAL LITERACY, FINANCIAL BEHAVIOR, AND RISK PERCEPTION - Dinda Karunia Putri; Kumba Digdowiseiso (SEAN Institute, 2023)
The purpose of this research is to analyze the effect of financial literacy, financial behavior and risk perception on interest in stock investment in students of management program Faculty of Economics and Business National University. This research is sourced from primary data obtained from respondents through the distribution of questionnaires. The research sample was 100 respondents with the method used was simple random sampling method. Descriptive analysis and multiple linear regression analysis are data analysis techniques used in this study with the STATA Statistics version 16 program. The results show that financial literacy and financial behavior variables have a positive and significant effect on investment interest, while risk perception does not and does not significantly affect investment interest in management study program students, Faculty of Economics and Business, National University